Load carrying capacity of dry floor panel system - Te, Chei Yean (2006)
This paper describes the application of finite element modelling to study structural performances of a dry floor system, consisting of plywood attached to top layer of profiled steel sheet by self-drilling, self-tapping screws connector. Parametric study was carried out by using various profiled steel sheet thickness, plywood thickness and different geometry of profiled steel sheet. The preliminary FE model was validated using experimental study. Parametric studies showed 96.72% increased in flexural stiffness when the thickness of profiled steel sheet was changed from 0.8mm to 1.8mm. The increment of plywood thickness from 9.5mm to 25mm has increased flexural stiffness of the slab up to 23.00% in a quadratic form. Different geometry of profiled steel sheet affects the load carrying capacity of the proposed dry floor panel where SDP gives 1.42 to 1.49 higher in flexural stiffness per 1 unit area of steel compared with PEVA. This means SDP profile will give more economical design compared with PEVA profile. A theoretical formula was proposed to predict the flexural strength of the slab. Moment capacity predicted from FE analysis preformed 1.06 safety factor over theoretical formula and 1.40 over experimental results. FE analysis had indicated high degree of accuracy and revealed that the prediction moment capacity using FE analysis and theoretical formula are conservative and safe for design purpose.It can be concluded that the proposed dry floor panel has a great potential to be exploited as alternative flooring system.